The importance of immunological tests in the diagnosis of patients with hereditary angiedema - Vieira, Thaynara Kamilly; Vivan, Rosália Hernandes Fernandes; Borin, Fabiane Yuri Yamacita (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No especial (2022): Farmácia, 2022)
Hereditary Angioedema (HAE) is a rare, autosomal dominant genetic disease with recurrent episodes of edema that can affect many parts of the body, and is often confused with common allergic conditions. This paper aims to highlight the importance of immunological examinations in the diagnosis of these patients through a bibliographic review from 2014 to 2018 in electronic and physical databases. Currently, to make the diagnosis it is necessary that the patient presents a main clinical criterion, family history and a laboratory criterion. Eliminating other alleged pathologies and establishing the correct diagnosis of HAE is of utmost importance. Immunological examinations are the key to closing the diagnosis and the path to safe and effective treatment, aiming at improving and relieving symptoms as well as preventing future events.